Analysis of the environmental sustainability of forest ecosystems of Poltava region - Taranenko, A.; Bocharov, D.; Korolkova, A.; Pryadko, V. (Scientific Progress & Innovations, 2025)
Forestry today faces a number of challenges related to environmental impacts and the use of forest resources. The threat of forest degradation from fires, illegal logging, pests and climate change is increasing. Issues related to the ageing of plantations, insufficient natural regeneration and disturbance of forest structure due to active resource use are particularly acute. At the same time, significant progress is being made in reforestation, particularly through afforestation and the promotion of natural regeneration. Forestry aims at a balanced management of forest resources, which includes the reproduction, protection and conservation of forests, as well as the introduction of new technologies for monitoring and preventing forest fires. However, in order to preserve forest ecosystems in the long term, it is necessary to improve management processes, raise environmental awareness and strengthen the responsibility of forest users. The Emerald Network is an initiative to conserve biodiversity in Europe and neighbouring regions, particularly in Ukraine. It is an integral part of the implementation of the Berne Convention and aims to protect the natural habitats of species of conservation concern. The main objective of the network is to create conditions for the conservation of rare and endangered species and key habitats, regardless of national borders. The Emerald Network makes it possible to identify valuable natural areas where action can be taken to protect them, and also ensures a balanced use of resources. However, the process of developing the network in Ukraine has certain shortcomings, in particular the lack of a sufficient inventory of species and habitats, and a lack of coordination between scientists and authorities. For the further success of this initiative it is important to establish cooperation at all levels: from scientific research to public discussion and implementation.